Assessment of the shoulder function of the dominant limb in female volleyball players aged 18-25 - Galinska, K.; Goslinska, J. (Acta Kinesiologica, 2020)
The assessment of the shoulder function of the dominant limb in female volleyball players aged 18-25 is a research work aimed at determining the relationship between the motor, postural and support function of the dominant and non-dominant limb in volleyball players and non-training women of the same age. Is the arm of the dominant located higher in relation to the other? Is it dependent on the position on the pitch? The research was carried out on 40 women, 20 in each of the research and control groups. During the examinations, each participant was made 4 photos on the posturographic grid, which were then analyzed according to selected methods and specific anatomical points. This allowed for an accurate assessment of the height of the acromion, and with this analysis of the posture of the female volleyball players. There were also 4 functional tests focused on the strength of the shoulder muscles and deep stabilizing muscles to show differences between the dominant and non-dominant limb. The results of the study show statistically differences in the positioning of the shoulder joint between groups, where p= 0.0009. In 17 of volleyball players the left joint is higher than the right one by an average of 1.60 cm. The group of volleyball players in all functional tests obtained a better average score, differing statistically significantly between groups. The obtained results allow to state that volleyball is a sport that largely affects the development of the shoulder girdle muscles on both sides of the body with attention to the increase in strength in the dominant shoulder.